Between Normativity and Social Benefit: A Socio-Legal Analysis of Gold-Based Fidyah Ritual in Jambi - Rahmi Hidayati; Maryani Maryani; Ruslan Abdul Gani; Muhammad Farhan; Amirulhakim Bin Ahmad Nadzri (Al-Qisthu, 2026)
The practice of gold-based fidyah rituals (daur) in Jambi Malay society creates legal ambiguity due to invalid contractual mechanisms and a shift in beneficiaries from the poor to religious elites. This study aims to analyze the dynamics of gold-based fidyah from the perspectives of Islamic jurisprudence, ḥīlah shar‘iyyah, and socio-legal utility. Employing a socio-legal research methodology, data were collected through in-depth interviews, field observations, and literature reviews. The study reveals that doctrinally, the symbolic grant stratagem renders the fidyah legally invalid under Islamic law. However, socio-legally, the practice persists as an adaptive mechanism to alleviate financial burdens while reinforcing communal solidarity and custom-sharia integration. The novelty of this research lies in highlighting the tension between Islamic legal formalisms and local cultural benefits. This study asserts the necessity of reforming fidyah practices to realign with sharia norms and social empowerment.